Relacjonowanie wyborów samorządowych w prasie regionalnej w 2010 roku. Komunikat z badań - Biskup, Bartłomiej; Churska-Nowak, Karolina; Drobczyński, Sebastian; Hess, Agnieszka; Kolczyński, Mariusz; Mazur, Marek; Piontek, Dorota; Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The paper presents the methodology and partial results of an empirical study on the professionalization and mediatization of the local government election campaign from the perspective of its coverage by the regional press. The study was conducted by a research team from four academic centers in Poland, under a research project entitled The elections to local governments in regional media. Regional dailies and television election programs as platforms of political communication. One of the aims of the project was to analyze how election campaigns were covered by local press at the time of the local government election campaign in Poland in 2010. Quantitative and qualitative methods of analysis were applied to the content of press releases concerning the elections collected over the last two weeks of the election campaign, prior to the elections of 21st November 2010, in the regional issues of the printed versions of “Gazeta Wyborcza” and regional variations of the “Polska The Times”, published in four regional capitals – Katowice, Kraków, Poznań and Warsaw. In the case of newspapers, an examined entity was a press release on the elections.